The Research on the Curriculum Design of Labor Education for Chinese Higher Vocational Students - Yijing , He; Jianhuang, Meng (Journal of Roi Kaensarn Academi, 2024)
One of the main goals of higher vocational education is to cultivate technical talents that meet social needs. Through labor education, students can not only learn professional skills, but also develop good professional qualities and better adapt to the future work environment. Constructing a student learning effect evaluation index system for labor education courses in higher vocational colleges in China is of great significance to the quality of education in higher vocational colleges and the overall development of students. Through the evaluation index system, students' learning outcomes in labor education courses can be measured more accurately, providing feedback to educators and helping them adjust teaching methods, thereby improving the quality of teaching. Through literature analysis, questionnaires, statistical analysis and other methods, this paper conducted an in-depth study of the student learning effect evaluation index system of labor education courses for higher vocational students in China, and systematically analyzed the specific situation of students in higher vocational colleges in Shaanxi Province, China. , the assessment indicator system and weight indicator system were redesigned. The student learning effect is scientifically quantified, and it provides some useful reference and help for the construction of student learning effect evaluation index system for labor education courses for Chinese higher vocational students.